Thought control study of medical students in Shimoga Institute of Medical Sciences (SIMS) - K, Jagadeesh; Revankar, Shreenivas P.; K. S., Ramprasad (International Journal of Research in Medical Sciences, 2017)
Background: Thought is a mental process which occurs in the Neo-cortex of the Brain [Cerebral cortices] based on the background knowledge, perception of the event or the action and understanding influenced by the individual traits or personality. Individual thoughts differ from person to person, time to time, and the events in life. Mainly thought is interpreted or understood based on the behaviour or when the person explains about it. Thought process in the brain can be acknowledged by an individual to have acceptable behavioural norms in the society, but cannot be explained by patients with disorder of thought processes. The behaviour of these individuals is acknowledged as the thought of the individual. Abnormal thought process occurs in psychiatric conditions like Psychosis, Anxiety disorder, Post traumatic disorder, mood disorders in varied manners. It also has implications or influences of the hormonal status and age of the person. In this study we are evaluating the thought control in the teenagers. Methods: the study was carried out in the medical students of SIMS-Shimoga. It is a questionnaire based study using a thought control questionnaire (TCQ). Results: The results were studied in five domains namely Distraction, Social, Worrying, Punishment and Re-appraisal, were found to vary within the acceptable limits and comparable with earlier studies. Conclusion: The findings in this study reflect the positive approach, handling of the unwanted and distracting thoughts in the teenagers.